Analysis of Changes in Students' Scientific Literacy Ability After Attending Lectures Using the RADEC Model - Wati Sukmawati; Zulherman Zulherman (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze Changes in Students' Scientific Literacy Ability in lectures on the basic concepts of science, the subject matter and the characters trained during lectures using the RADEC model (Read, Answer, Discuss, Explain, and Create) using the Rasch model stacking analysis. This descriptive research is a quantitative study with a sample of 42 first year students. The data were obtained from scientific literacy tests, then the data were analyzed using the Rasch model stacking analysis. The results showed that students with low and high abilities experienced changes in scientific literacy skills for the better. During learning with the RADEC model students are trained to study independently and in groups at the read and answer stages, students are also trained to express opinions and learn to accept opinions from other friends during the discuss and explain stages. At the create stage, students are facilitated in applying material concepts to solve problems in everyday life so that students are trained in scientific literacy.